Effects of different levels and duration of energy diets on oestrous behaviour of crossbred cows - A., Azizah; Yaakub, Halimatun; Sukardi, Sabrina; Jusoh, Ahmad; Ab. Jalal, Izuan Bahtiar (2009)
Oestrous behavior was used as an indication to conduct artificial insemination (A1) in the female mammal. Thirty six crossbred Kedah-Kelantan (KK) cows were divided into two treatment groups; a single maintenance (GSM) and double maintenance, (GDM) energy level feed based on body weight requirement. Oestrous was synchronized using a chloprostenol intra vaginal progesterone releasing device (CIDR-B®). The cows were observed for 72 hours beginning at CIDR-B® removal. No differences were observed between GSM and GDM (P>0.05) in the first cycle of oestrous. However, the GSM group showed significant differences in vagina discharge and mounted behaviour (P<0.05) in the second cycle. In conclusion, higher and longer duration of energy levels did not support the oestrous behaviour of cows in the present study.